Skiing's Physiological Foundation (International Journal of Food and Nutritional Sciences, 2022)
Alpine ski racing is a challenging sport to examine because of the harsh cold, altitude, andplexity.This review includes 29 on-snow examinations of specific physiological aspects of the major ski racing disciplines, nine off-snow investigations of the physiological capacity of ski racers of different skill levels, four review papers, and 430 years of research. Alpine ski competitions appear to include the intricate integration of numerous physiological systems, none of which may be more crucial to performance than the others. Although technical skill seems to have the biggest impact on performance, the capacity to maintain technical proficiency over the course of a lengthy competition season necessitates excellent skills throughout all physiological systems. Sport scientists must figure out the best method and window of time to build these systems simultaneously. For the purpose of determining aerobic and anaerobic needs and abilities, additional research using portable, modern investigative instruments is needed, particularly in the areas of muscle function and relative energy system contribution during both single- and multi-runs over different terrain.